Pengaruh Layanan Website Tokopedia Terhadap Kepuasan Konsumen Menggunakan Metode Webqual 4.0 - Sri Andayani (Universitas Katolik Musi Charitas, 2018)
Selling transactions of goods or services with computer network media connected to the internet is called e-commerce. The development of e-commerce in Indonesia is very high due to the huge population of Indonesia. Tokopedia is one of the most popular e-commerce in Indonesia currently in the form of a marketplace. The purpose of this study was to determine customer satisfaction with the quality of the Tokopedia website using the webqual 4.0 model and the benefits of this study were to provide input for Tokopedia managers in improving service to consumers. The results of this study are usability quality has a negative influence, information quality variables (information quality) and service quality variables (service quality) have a positive influence on user satisfaction.